The Effect of Introducing a Non-Redundant Derivative on the Volatility of Stock-Market Returns When Agents Differ in Risk Aversion - Bhamra, Harjoat S.; Uppal, Raman (Review of Financial Studies, 2009)
We study the effect of introducing a nonredundant derivative on the volatilities of the stock market return and the locally risk-free interest rate. Our analysis uses a standard, frictionless, full-information, dynamic, continuous-time, general-equilibrium, Lucas endowment economy in which there are two classes of agents who have time-additive power utility functions and differ only in their risk aversion. Our main result is to show analytically that if the intensity of the precautionary demand for savings is not too high, then the introduction of a nonredundant derivative increases the volatility of stock market returns. Furthermore, in the economy with the derivative, the volatility of stock market returns can be substantially greater than that of aggregate dividend growth (fundamental volatility). We also show that the volatility of the locally risk-free interest rate increases with the introduction of the derivative.